Energy‐efficient cooperative predictive control for multi‐agent non‐linear systems with transmission delay. Issue 17 (1st November 2019) - He, Defeng; Lu, Liangye; Luo, Renshi; Zhang, Wenan
Abstract : This study proposes a novel distributed economic model predictive control (EMPC) strategy for energy‐efficient cooperative formation of decoupled multi‐agent non‐linear systems with transmission delay. In this system, each subsystem is controlled to maximise the economic performance during tracking the reference trajectory and maintaining its relative position to the neighbouring subsystems. The cooperation between subsystems is executed through the cost functions and coupled constraints associated with the delayed information. A Lyapunov‐based contractive constraint is introduced to establish recursive feasibility of the proposed EMPC strategy. Moreover, stability of any single subsystem with the EMPC is proved rigorously by exploiting the idea of input‐to‐state stability and for both strongly and weakly connected networks, stability of the whole system is then proved by using the generalised small gain condition. The effectiveness of the proposed strategy is illustrated by two numerical simulation experiments.